Construction of an occupational therapeutic practice with children with developmental delay: Experience report (Research, Society and Development, 2022)
Objective: This study aimed to understand how the therapeutic practice is structured, whose objective is to promote the occupational professional of children with AD in their activities. Methodology: This is an experience report built from experiences in the subject Supervised Internship in Occupational Therapy 1, taught in the seventh period of the Occupational Therapy course at the Federal University of Pernambuco (UFPE), in a non-profit institution located in the Recife neighborhood. Weekly consultations were carried out with children with different diagnoses, such as Down Syndrome and Autism Spectrum Disorder. Results and Discussion: The interventions were structured gradually, starting from the application of anamnesis and estimates with the family and the child. Employment was used as a tool to promote bonding and the development of functional skills for occupational performance. From the analysis of evolutions, it was verified the improvement of skills not previously explored by the individual that favored the execution of actions. Conclusion: Due to the short period for the observation of the instruments, the qualitative result of this evolution was not obtained. However, the potential of therapeutic activity is perceptible through a practice carried out in a gradual and structured way, using an application of instruments formed from instruments, from the training of individuality, to the development of professional training.